PENGARUH PENYULUHAN TERHADAP PERILAKU PEDAGANG GORENGAN TENTANG BAHAYA PENGGUNAAN KERTAS KORAN BEKAS SEBAGAI KEMASAN GORENGAN DI DAERAH ASRAMA HAJI MEDAN - Purnawati Nainggolan; Jumirah .; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Secondhand newspapers are the material commonly used for packing food. However, secondhand newspapers are not safe to used for packing fried food because the ink used for printing on newsprint paper contains Lead and can move into fried by the oil. The low knowledge of fried food sellers about the dangers of using secondhand newspapers as packing fried food can threaten the health of consumers. The objective of the study was to determine the influence of extension about the dangers of using secondhand newspapers as packing fried food to the behavior of sellers in Asrama Haji Medan. The result of this study showed that before extension 50% of fried food sellers have medium knowledge and after extension increases become 72,7%. Before extension 9,1% of the fried food sellers have good attitude and after extension increases become 36,4%. Before extension 9,1% of fried food sellers have good action and after extension increases become 27,3%. Based on the results of the study, it can be concluded that extension with individual approach and media leaflet can increase the behavior of fried food sellers about the dangers of using secondhand newspapers as packing fried food. Therefore, researcher suggest to BPOM to give a extension to fried food sellers with individual approach and media leaflet to change the behavior of sellers be better and further enhance the dissemination activities about the dangers of using secondhand newspaper as packing fried food that the information to public. Keywords: behavior, secondhand newspaper, fried food seller